Modeling and forecasting: A case study of tourist arrivals in Malaysia - Abd Rahman, Nur Haizum; Jamal, Nur Nabilah; Abd Rahman, Nur Hidayah (Kulliyyah of Languages and Management, International Islamic University Malaysia, 2019)
Tourism industry has become one of the main sources for Malaysia's income. It affects other sectors such as hotels, retail businesses and transportations. Thus, it is important to monitor the development of tourism industry, so that proper planning can be enforced. Therefore, forecasting by using time series analysis, which is the Box-Jenkins method will be discussed here to provide future information to support the decision-making processes. The forecast performance has been compared by using magnitude error measurements. The empirical result shown that SARIMA (0,1,0)(0,1,1)12 is the best model in forecasting tourist arrivals with only 8% different between 12 of the actual and forecast values.